2015
DOI: 10.1007/s00198-015-3026-0
|View full text |Cite
|
Sign up to set email alerts
|

US Preventative Services Task Force FRAX threshold has a low sensitivity to detect osteoporosis in women ages 50–64 years

Abstract: We found that the USPSTF-recommended MOF risk threshold of 9.3 % for osteoporosis screening in women ages 50-64 years old has a low sensitivity to detect osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 10 publications
1
16
0
1
Order By: Relevance
“…0.71-0.80; I 2 = 93.2%; 7 studies [7798 participants]); for the Male Osteoporosis Risk Estimation Score, the pooled AUC was 0.80 (95% CI, 0.71-0.88; I 2 = 97.6%; 3 studies [4828 participants]). AUCs for FRAX could not be pooled but ranged from 0.58 26 to 0.82. 26 AUCs in younger women (<65 years) varied from 0.58 26 to 0.85.…”
Section: Clinical Risk Assessmentsmentioning
confidence: 99%
“…0.71-0.80; I 2 = 93.2%; 7 studies [7798 participants]); for the Male Osteoporosis Risk Estimation Score, the pooled AUC was 0.80 (95% CI, 0.71-0.88; I 2 = 97.6%; 3 studies [4828 participants]). AUCs for FRAX could not be pooled but ranged from 0.58 26 to 0.82. 26 AUCs in younger women (<65 years) varied from 0.58 26 to 0.85.…”
Section: Clinical Risk Assessmentsmentioning
confidence: 99%
“…7,22 Accordingly, we found that postmenopausal women aged 50 to 64 who developed a screening-level FRAX were unlikely to have a hip or clinical vertebral fracture before age 65. Like past studies, 7,8 our results do not support routine use of FRAX to identify candidates for screening in postmenopausal women aged 50 to 64.…”
Section: Discussionmentioning
confidence: 79%
“…The FRAX score (https://www. shef.ac.uk), while carrying some limitations and having a lower sensitivity and specificity for younger patients [87], is validated, readily available, and easily administered to patients. However, the actual utilization of FRAX is poor, with the USA performing 11,807 calculations per 1 million people over the age of 50 [88].…”
Section: Denosumabmentioning
confidence: 99%